Mass Platooning: Information Networking Structures for Long Platoons of Connected Vehicles - Mahdi Razzaghpour; Babak Ebrahimi Soorchaei; Rodolfo Valiente; Yaser P. Fallah (IEEE Open Journal of Intelligent Transportation Systems)
Investigating Vehicle-to-everything (V2X) communication, we dive into the concept of vehicle platoons, a key innovation in transport systems, introducing a new era of cooperative driving. This new approach is designed to enhance fuel efficiency and improve overall traffic flow. Crucially, the success of this system relies on keeping vehicles at closely monitored distances, particularly at high speeds, which depends on rapid and reliable data exchange among vehicles through a wireless communication channel that is intrinsically unstable. The possibility of improving platoon efficiency through wireless data exchange is clear, but addressing network issues such as data loss and delays is crucial. These problems can compromise platoon functionality and need careful handling for real-world applications. Present platooning models also struggle with forming ‘long’ platoons with multiple vehicles due to the limited range of Vehicle-to-Vehicle (V2V) communication. Quick and efficient traffic information sharing is crucial to ensure vehicles have adequate time to respond. Given the safety-critical nature of these communications, both reliability and ultra-low latency are essential, particularly in platooning contexts. To address these challenges, we suggest a distance-based, network-aware relaying policy specifically for long platoons of connected vehicles. The results of our simulations indicate that this relaying approach significantly decreases communication breakdowns and narrows the error gap between vehicles, all achieved with only a slight increase in computational demand.